Polypropylene blend with charcoal / Zuliana Mohd Arifin - Mohd Arifin, Zuliana (2008)
The effects of the presence of charcoal in polypropylene polymer blends w ere studied. This was the first attempt to produce new composite in industry by using charcoal incorporated into polypropylene polymer blends. Five type of testing had been done and conducted to determine the properties of the composite of polypropylene-charcoal. There were tensile strength, impact testing, Differential Scanning Calorimeter, Fourier Transform Infrared Spectrometer and flammability test. In this study, thermoplastic composites were made from blending virgin PP pellets with the charcoal by melt compounding and then compression molding. The mechanical properties and functions of these composites were investigated. The compositions of blended ratio were also studied in this work. The results show that the mechanical properties of the PP with 5 wt% charcoal composites were better than that of the PP composites with 10, 15 and 20 wt% of charcoal composition. The cystallinity of polymer blends decreased compared to neat PP. From flammability test, it was found that this composite was not suitable be used as flame retardant.